Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1161/circulationaha.107.757781
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Induces Human Leukocyte Antigen-G Expression in Vascular Endothelial and Smooth Muscle Cells

Abstract: Background-Human leukocyte antigen-G (HLA-G) expression in heart transplant patients has been negatively associated with acute cellular rejection and cardiac allograft vasculopathy. We assessed HLA-G expression in vascular human endothelial and smooth muscle cell cultures to determine if future therapeutic agents can be targeted toward inducing HLA-G expression to protect against allograft rejection and vasculopathy. Methods and Results-Human coronary artery endothelial, aortic endothelial, and coronary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Interestingly, cell-surface and circulating HLA-G isoforms have also shown to be protective through inhibition of immune responses directed against the allograft endothelium. We have recently shown that HLA-G can be upregulated in human endothelium cells in vitro, 36 which might represent a strategy to protect against immune-mediated endothelial damage post-transplant. The present findings suggest a disproportionate HLA-G expression after two different anti-proliferative strategies, namely RAD or MMF.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cell-surface and circulating HLA-G isoforms have also shown to be protective through inhibition of immune responses directed against the allograft endothelium. We have recently shown that HLA-G can be upregulated in human endothelium cells in vitro, 36 which might represent a strategy to protect against immune-mediated endothelial damage post-transplant. The present findings suggest a disproportionate HLA-G expression after two different anti-proliferative strategies, namely RAD or MMF.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic conditions may profoundly affect endothelial cells through a cascade of reactions involving neutrophils (Sumagin et al, 2006(Sumagin et al, , 2008Butler et al, 2008;Carpenter and Alexander, 2008;Hu et al, 2008) and smooth muscle cells (Michiels et al, 2000;Aley et al, 2008;Jernigan et al, 2008;Mayr et al, 2008;Osada-Oka et al, 2008a, 2008bSheshgiri et al, 2008). Hypoxia regulates the expression of many genes, and the list of hypoxiarelated genes is growing (Yoshida et al, 2006;Eckardt et al, 2007;Said et al, 2007;Wang et al, 2007;Chen et al, 2008;Furuta et al, 2008;Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The MLR shows high levels of cytotoxicity with only one donor, possibly because the recipient's NK-CTLs and those of the donor do not share their HLA-G alleles; but more studies are needed to elucidate this point. HLA-E loaded with a peptide derived from the leader sequence of allogeneic HLA-G molecules (expressed in the allograft cells) can be recognized by CD8+ T cells by means of their TCR, inducing the activation of cytotoxicity, the secretion of cytokines, and eventually the production of antibodies, which leads to graft rejection-all, as shown in Figure 2. HLA-G was shown to be expressed by endothelial cells and its expression and secretion upregulated in a dose-dependent manner by progesterone [79]. The induction of HLA-G expression in endothelial cells of the allograft can clearly benefit the patient by inhibiting effector cells responsible for rejection and vasculopathy.…”
Section: Hla-ib Endothelium and Transplantationmentioning
confidence: 99%